HAZ toughness of Ti-microalloyed ofshore steel in as-welded and simulated condition - Rak, Inoslav (Kovine zlitine tehnologije, 1995)
The CTOD values measured on 34 mm thick SENB specimen taken from multipass 1/2K joints were compared with the values obtained from 8 mm thick SENB specimens with simulated microstructures of CGHAZ (a/W=0.5). Single and double thermal cycles were used to simulate various thermal treatment which HAZ at the weld bond may xperience during the welding.
Keywords: jeklo; mikrolegirano jeklo; varjenje; žilavost